Potential Use of Polysaccharides natural polymer in plants as an alternative to chemical Enhanced Oil Recovery (EOR) to Increase Oil Production in Indonesia - Syariefudin, Muhammad Irtin; Muslim, Muslim (Green Publisher Indonesia, 2023)
The decline in oil production in the past few decades has made Enhanced Oil Recovery (EOR) one of the technologies that get more attention because it has been proven to increase oil production in a field. One EOR method that is widely used today is by injecting chemicals in the form of polymers. Polymers themselves are grouped into two types, namely synthetic polymers and natural polymers or known as biopolymers. The use of synthetic polymers has limitations, especially in oil reservoirs that have high temperatures and salinity levels, therefore the development of biopolymers is an interesting thing to study, in addition to the availability of raw materials in large quantities, this type of polymer has good mechanical properties and is easy to make derivatives according to the desired properties and characters. The use of biopolymers is considered cheaper and safer because they come from natural materials so that they can be decomposed properly. Therefore, the researcher tried to make a comprehensive brief review of the reasons for the importance of using polymers in EOR activities in Indonesia, a comparison of the properties, characteristics, advantages and disadvantages of the two types of polymers, along with the progress of several research results that have been carried out previously. this research is expected to provide useful insights about the potential use of natural materials as basic materials in the process of making biopolymers, properties and characteristics that are resistant to bacteria and high salinity.